Psychological features of emotional experiences in primary school age - Dmitriyuk, Natalia (Psychological Prospects Journal, 2022)
Purpose. This article provides a theoretical analysis and empirical verification of the position that emotional experiences are an important factor in the holistic mental development of primary school children.Methods. Theoretical psychological analysis of the phenomenon of connection of emotional experiences with the integrity of the personality and its harmonious development. On the basis of the carried out theoretical researches and generalizations the program of empirical check of certain positions which is realized through projective methods has been developed.Results. The theoretical review of the subject of research in the scientific literature revealed that experiences can be considered as a personal, individual phenomenon that arises with the emergence of the process of understanding and determined by the consciousness of the individual and has an important impact on his mental development. According to researchers, the period of primary school age is important in the life of a growing person, because all events are projected through the trajectory of emotional experiences and have a decisive impact on the mental development of the individual. The conducted empirical research allowed to confirm the opinion of scientists that the main factors determining the level of mental development of the personality of a junior high school student include the interest and specificity of emotional experiences of schoolchildren in the process of their inclusion in educational activities. Consequently, students with a high level or index of emotional experiences are more pronounced negative emotions, anxiety, malaise, they find it difficult to control their emotional state. This often leads to emotional maladaptation, conflict with peers and adults.Conclusions. The paper analyzes that emotional experiences provide the process of formation, transformation and development of personality through significant objects, phenomena and other subjects. It is proved that reducing the dynamics of negative emotional experiences, achieving a certain level of confidence has a positive effect not only on the process of acquiring knowledge, skills and abilities, but also on the personal development of junior sheol.